Using AI Tools in Thesis Writing: Perspectives from EFL Students and Lecturers - Jaya, Sinarman; Melati; Ahmad, Norkhairi (International Journal of Language Pedagogy, 2025)
Digital writing tools have become increasingly common in academic settings, yet their impact on the thesis writing process, especially in English as a Foreign Language (EFL), remains underexplored. This study examined the use of digital writing tools in thesis writing from the perspectives of EFL students and lecturers at four universities in Bengkulu, Indonesia. A mixed-methods approach was used, combining quantitative data from surveys with qualitative insights from semi-structured interviews. The instruments, which included a student survey and a lecturer interview protocol, were validated through expert review and pilot testing before being administered. The survey involved 200 undergraduate students. Additionally, 20 students and 8 lecturers participated in interviews. Data were analyzed using descriptive statistics to quantify student perceptions and experiences, while thematic analysis was applied to the qualitative interview data to identify key themes. The findings revealed that students found AI writing tools useful across various stages of the thesis writing process, particularly for idea generation and language refinement. However, concerns arose regarding overdependence, ethical issues, and insufficient institutional support. Lecturers acknowledged the benefits and challenges AI tools present to academic integrity and writing development. This study offered a more comprehensive understanding of how digital tools influenced academic writing in EFL contexts. It highlighted the need for clear institutional policies and pedagogical strategies to guide their use. Future research could examine the long-term impacts and cross-contextual applications of AI writing tools in the academic setting.